ABCs of z/OS system programming Volume 1 - Rogers, Paul (IBM Corp., 2011)
The ABCs of z/OS System Programming is a 13-volume collection that provides an introduction to the z/OS operating system and the hardware architecture. Whether you are a beginner or an experienced system programmer, the ABCs collection provides the information that you need to start your research into z/OS and related subjects. Whether you want to become more familiar with z/OS in your current environment, or you are evaluating platforms to consolidate your e-business applications, the ABCs collection will serve as a powerful technical tool.
Includes bibliographical references
Keywords: z/OS; Operating systems (Computers); Z/OS; Systèmes d'exploitation (Ordinateurs); operating systems